Maximal power output and perceptual fatigue responses during a Division I female collegiate soccer season - McLean, B. D.; Petrucelli, C.; Coyle, E. F. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to investigate how maximal power output (PMAX), as measured via the inertial load cycling technique, changes throughout a collegiate soccer season in relation to training load completed. The current investigation took place throughout the 2010 Big XII soccer season. Nineteen Division I female collegiate soccer players (age: 19.9 ± 1.2 years, stature: 165.1 ± 6.6 cm, mass: 61.0 ± 6.8 kg) from the same team completed regular inertial load cycling tests and perceptual fatigue questionnaires throughout the season. Players were divided into STARTERS and NON-STARTERS based on percentage of matches started throughout the season. The results demonstrated that STARTERS experience much greater load throughout the season than NON-STARTERS (2247 ± 176 arbitrary units [AU] and 1585 ± 174 AU, p < 0.05), accounted for by increased load during matches. This increased load throughout the season was accompanied by decline in PMAX in STARTERS (to 92.3 ± 6.6%, p < 0.05), whereas PMAX was maintained in NON-STARTERS for the duration of the season (99.0 ± 4.9%). Furthermore, STARTERS experienced greater muscle soreness throughout the in-season period compared with NON-STARTERS. The main finding of this study is that PMAX declined throughout the middle and latter parts of the season in STARTERS, after experiencing significantly greater match loads than NON-STARTERS throughout the season. The current findings, combined with previous investigations, suggest that load needs to be carefully monitored throughout the in-season period to maintain optimal neuromuscular performance throughout a team's entire sporting season.Whole-body vibration is an emerging strategy used by athletes and exercising individuals to potentially accelerate muscle recovery. The vibration elicits involuntary muscle stretch reflex contractions leading to increased motor unit recruitment and synchronization of synergist muscles, which may lead to greater training adaptations over time. Intense exercise training, especially eccentric muscle contractions, will inevitably lead to muscle damage and delayed onset muscle soreness, which may interfere with the maintenance of a planned training program. Whole-body vibration before and after exercise shows promise for attenuating muscle soreness and may be considered as an adjunct to traditional therapies (i.e., massage, cryotherapy) to accelerate muscle recovery.